Non-Cash Payment Instruments: Perception of Muslim Community Sambas Regency, West Kalimantan - Sri Deti (Jurnal Ilmiah Ekonomi Islam, 2022)
This study aims to reveal how sambas Muslim community's perception of non-cash payment instruments and see what non-cash payment instruments are most widely used by Muslim people in Sambas Regency. This study uses a quantitative approach, where data collection is done by disseminating questionnaires online to the Muslim community in Sambas District which is then measured using a Likert scale. The number of samples was determined using a Slovin formula with a significant rate of 7.9% so that 160 respondents would fill out the questionnaire. The sampling techniques used are random sampling. The results of this study show that the Sambas Muslim community has a good perception of the availability of infrastructure, usefulness, and promotion conducted by Sharia banks related to non-cash payment instruments. In addition, the Sambas Muslim community also realizes that using non-cash payment instruments has two sides that must be considered, in addition to having many advantages must also remain careful to avoid or minimize the risks that can befall at any time. It is recommended to the next researchers to conduct research using more in-depth analysis to see the influence of the use of non-cash payment instruments on various aspects in Sambas Regency.